Nonlinear Vibration Analysis of Tubing Strings in Underground Gas Storage Using Multiscale Wavelet Transform. (6th May 2019) - Yan, Hang; Yan, Yifei; Yan, Xiangzhen
Abstract : The tubing string exposed to transient flow may undergo nonlinear vibration due to sudden change in pressure in conveying gas. But, the drag on such structures often leads to fatigue failure of the strings that may significantly affect the vibrations through the combined effects of the first sections of gas injection, annulus pressure, the inclined structures, and the large transient flow component. In this paper, the nonlinear vibration analysis of tubing strings in underground gas storage using the multiscale wavelet transform has been studied. The vibration characteristics of strings in the steady gas injection process have been analyzed by numerical simulation. Results of the calculation model are compared to numerical ones reported previously, and the excellent agreement is obtained. The nonlinear vibration experiment of strings in the gas injection process has been studied for discussing the change rules of the string pressure, the wall velocity, and the amplitude in the gas injection process. The results show that the near-injection port section and the inclined section of strings are the high-incidence areas of nonlinear vibration of strings in underground gas storage. We also find that significant alteration of the dynamics is due to low-frequency pressure fluctuation forces on the tubing strings.